Blekok Bird and City Development - Mila Mardotillah; Adi Junjunan Mustafa; Anwari Masatip; Rini Soemarwoto; Lablu Barua (Politeknik Pariwisata NHI Bandung, 2025)
Blekok Sawah with the Latin name Ardeola speciosa is one type of bird from Ardeidae family. In the rice fields of Blekok Sawah, it is useful as a controller for insect pests and for seasonal change instructions by farmers. One of the extensive rice fields is in Ranca Bayawak village Bandung City. In 1975 Blekok flocks came looking for food in the rice fields until now. Besides Blekok birds, there are also birds namely egrets (Bubulcus ibis) with black and white beaks. Bamboo and selong trees are the resting places for the birds. On the tree, these animals live side by side to make many cages for laying eggs. The birds’ habitat are maintained based on the Regional Regulation of Bandung City No. 11 of 2005 concerning forbidden to damage the place of residence and kill or trade the two species of birds because it could face a fine of Rp.5 million plus other administrative sanctions. The rapid development of the city of Bandung in the last five years has caused a lot of land conversion and slowly affected the existence of Blekok in Ranca Bayawak Village. Residents are increasingly difficult to find the noise of birds in the afternoon replaced by the hustle and bustle of city development. This research uses qualitative descriptive research method to explore how the existence of blekok birds along with the development in the last 5 years. By knowing the existence of Blekok birds in the last five years, we can assess whether the adaptation of Blekok Bird to the environmental changes that occur in their habitat.